FEATURES OF THE ADAPTABILITY OF MILITARY SERVANTS - Теслюк, Валентина; Морус, Тетяна (SWorldJournal, 2023)
The article establishes that the successful adaptation of combatants to peaceful life is defined as resilient reintegration. Peculiarities of adaptability of military personnel were studied. It was found that a sufficient level of adaptation is observed i